RC column failure probabilities to blast loads - Hao, Hong; Stewart, M.; Li, Z.; Shi, Y. (Multi-Science Publishing Co. Ltd., 2010)
Structural reliability analyses are commonly applied to estimation of probabilities of structural damage to static and dynamic loads such as earthquake, wind and wave loads. Although blast loadings acting on structures from accidental explosions or hostile bombings are very difficult to be accurately predicted owing to many uncertain parameters that influence explosion shock wave propagation and shock wave interaction with structures, reliability analyses of structural failure to blast loadings with consideration of uncertainties in blast loading and structural parameters are very limited. Instead, a large safety factor is usually used to account for uncertain variations in blast loading and structural parameters in blast-resistant design and analysis. This may lead to an inaccurate design of structures to resist blast loads, and an inaccurate assessment of structure performance in a given explosion scenario. In this study, reliability analyses of three example RC columns to randomly varying blast loads are carried out. The column dimensions, reinforcement ratios and material strengths are assumed to be normally distributed with the respective design parameters as the mean values. The mean value and standard deviation of the peak reflected pressure and duration of the blast load at various scaled distances are derived from available empirical formulae, and are used in this study to model the blast pressure variations. Failure probabilities of the example RC columns subjected to blast loads of different scaled distances are estimated. Numerical results are compared with those obtained with the deterministic blast loading or deterministic column property assumptions. The importance of considering the random variations of structural properties and blast loadings in assessing the blast load effects on RC columns is discussed.